Does caffeine really improve maximum strength performance? - Mathias, T. R.; de Lima-Junior, D.; de Melo, L. S.; de Lira, H. A.; de Oliveira, L. M.; Farah, B. Q.; Vasconcelos, G.; Beltrão, N. B.; Pirauá, A. L. (Medicina dello Sport, 2021)
BACKGROUND: It is recommended that caffeine is not used before repetition maximum strength tests. However, the effect of using caffeine was not tested yet. This article analyzed whether the caffeine supplementation improves bench press one-repetition maximum test (1RM) performance. METHODS: It is a pre-experimental, single-moment, crossover, counterbalanced, double-blind study. Twenty men (age 23±3 years; body mass 77.72±6.68 kg; height 1.77±0.06 cm; body mass index 24.77±1.57), experienced in resistance training (5.8±2.93 years), performed four visits to the laboratory; baseline assessments and 1RM familiarization composed the first visit. All subjects underwent 1RM in three following conditions: caffeine supplementation (420 mg), placebo intake (420 mg cornstarch), given 45 minutes before the start of the test, and control. According to data analyses, ANOVA One Way was performed, and the level of significance was set at P=0.05. RESULTS: It was verified there were no significant differences in the maximum strength between the conditions (F[2,4]=0.011; P=0.99), and the average loads obtained in each of them were 96.6±19.55 kg for caffeine supplementation, 96.9±18.46 kg for placebo intake, and 96.00±19.04 kg for control. CONCLUSIONS: Caffeine intake does not affect maximal strength performance for a scapular girdle and upper limbs in trained men. Thus, it is unnecessary to recommend deprivation of caffeine use before the application of the 1RM test.